Delivering group CBT- competencies and group processes - Satwant Singh (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Cognitive Behavioural therapy (CBT) is an empirically validated psychotherapy and the most researched therapeutic modality t has shown to be effective in treating a range of psychological disorders. Group therapy a common and powerful modality of treatment is being increased in popularity due to its evidence base and cost effectiveness. CBT group treatment models have been adapted from the individual treatment models unlike traditional psychotherapy modalities that focus on the group process as a medium of change. Current training in CBT and the assessment of CBT competencies using validated measures do not focus on the development of the core competencies for group therapy facilitation as traditionally CBT has been offered as individual based therapy. These core competencies utilities the group processes to modulate change. There are similarities and differences between group therapy and CBT. The combination of group processes and the manulised CBT approach can add benefit to provision of group based CBT. There is a need for development of further training, development of a validated assessment tool on CBT group therapy and supervision for CBT therapist to skill therapist in provision of group therapy focussing on group processes as a medium of change. [JCBPR 2014; 3(3.000): 150-155]